Stikes Yarsi Alumni Motivation as Care Worker to Japan Through Kaigo Fukushi-Shi Peer Support - Harlina Putri Rusiana; Istianah; Lalu Amri Yasir; Dewi Nur Sukma Purqoti (Journal of Health Science Community, 2021)
Nursing graduates are increasing but job opportunities are limited. It’s problem in many regions of Indonesia. Many work as voluntary with lower income. Meanwhile, Japan need for nurses as Kaigo Fukushi-shi is very high. Through the Indonesia-Japan Economic Partnership Agreement (IJ-EPA) program was made send 1,000 care workers every year. However, only 826 people in the span of 3 years went through the G to G program. This study aims to measure the level of motivation of STIKES YARSI Mataram graduates before and after received assistance through the Kaigho Fukushi-shi Peer Support. The method in this study is a Quasy Experiment without a control group with 25 sample. p-value 0.000 with a positive value of motivation. It’s concluded that there is an influence of the Kaigho Fukushi-shi Peer Support on the motivation of graduates to work in Japan. This research contributes graduates to gain experience working in Japan.